Perancangan Gedung Auditorium Universitas Almuslim Arsitektur Simbolis (Tangible Metaphor) - Munandar, Aris; Zuraihan, Zuraihan; Idayani, Idayani; Muhajirin, Muhajirin (Jurnal Sains Riset, 2025)
The design of the Almuslim University Auditorium aims to create a representative and functional facility to support academic, non-academic, and cultural activities. The auditorium will serve as a central venue for important events such as seminars, conferences, and artistic performances, as well as a space to enrich students' learning experiences and interact with the internal and external community, as well as the public. However, Almuslim University currently lacks an auditorium that meets the required standards, which hinders the execution of major events. Therefore, the main goal of designing this auditorium is to enhance facilities and provide adequate space. The design process began with a literature review to identify auditorium design standards related to acoustics, seating layout, circulation, and multimedia technology. This was followed by benchmarking through library and online sources. The next step involved identifying issues that arose during the design process and conducting a thorough analysis. This analysis aims to provide a design response that suits the environment and physical characteristics of the building. The results of this analysis are then implemented into the auditorium design concept with the theme of "Tangible Metaphor" or "Symbolic Architecture," integrated with modern concepts and additional architectural elements in the building design.